A DESCRIPTIVE STUDY ON STUDENTS’ ANXIETY IN SPEAKING SKILL AT SMP ISLAMIC SUNAN GUNUNGJATI - Wulan Wangi; Sindy Alfiatur Rofiah; Sutami Dwi Lestari (LUNAR, 2024)
Speaking is one of the important skills that must be mastered by students. Those who have low communication skills will have difficulty in expressing their thoughts, and they feel anxiety when they speak in front class. These problems should be addressed immediately. Based on these problem, the researchers conducted the study about finding the level of students' anxiety in speaking skills and the types of students' anxiety in speaking skills. The respondent in this study was the students in VII B at SMP Islamic Sunan Gunungjati. This study used a quantitative descriptive method. The instrument used in this study was a questionnaire sheet to obtain the instrument. Based on the results of the research, it can be concluded that the level of anxiety in students' speaking skills at SMP Islamic Sunan Gunungjati is "high”. The students had difficulties in speaking skills because they felt anxiety, had lack of confidence, and were afraid doing mistaken when they were speaking English in front of the class. Then, the type of student anxiety in speaking skills at SMP Islamic Sunan Gunungjati is "trait anxiety". Therefore, the anxiety level of students' speaking skills at SMP Islamic Sunan Gunungjati is at the "high" level and is included in the type of "trait anxiety".